Desain Model Pengembangan Diklat Gizi yang Efektif untuk Masyarakat Marginal - Atiek Zahrulianingdyah (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2013)
The purposes of this research is to describe and set-up the development model for organizing education and training of nutrition, assesst the effectiveness of teaching learning on the model for organizing education and training of nutrition. This research involved sample of 60 mothers from 286 mothers by using technique of purposive cluster random sampling. While data analyse used percentage description and the effectiveness of teaching learning model for education and training of nutrition by research design of â€œOne-Group Pre Test â€“ Posttest Designâ€, which used Paire t test. The research result shown that the factual model was very rarely implemented, since it was delivered incidentally by the women group of Family Welfare Education at the Level of Village as the Instruction of subdistrict level. The development model found 4 (four) steps of conceptual models, are: 1) planning; 2) organising; 3) acting/implementing, and 4) evaluating. Teaching learning shown implementing high effectiveness, as evidenced by the significant difference of result between before and after training, which Tscore is 13,246 while Table is 2,861 (Tscore> ttable). There is a decrease in iron anemia rates between before (40%) and after training in nutrition (20%), and sifnificant difference on tscore>ttable. Researchers suggested that need a post â€“ training assisstances in nutrition and empowerment from the leaders community and team driving the PKK to carry out a balanced diet in everyday family meals.ABSTRAKÂ Penelitian ini bertujuan untuk mendeskripsikan dan membangun model pengembangan pengorganisasian pendidikan dan pelatihan gizi, menguji keefektifan pembelajaran pada model pengorganisasian pendidikan dan pelatihan gizi. Sampel berjumlah 60 ibu dari 286 ibu dengan teknik purposive cluster andom sampling. Analisis data menggunakan deskripsi persentase dan keefektifan model pembelajaran pendidikan dan pelatihan gizi dengan desain penelitian â€œOne-Group Pretest-Posttest Designâ€, menggunakan uji beda (paired t test). Hasil penelitian menunjukkan bahwa model faktual amat jarang dilakukan Â dan bersifat insidentil karena diberikan oleh kader PKK atas instruksi dari tingkat Kecamatan. Model pengembangan yang ditemukan adalah model konseptual 4 (empat) langkah, yaitu: 1) perencanaan; 2) pengorganisasian; 3) penggerakan; dan 4) evaluasi. Pembelajaran memiliki efektivitas yang tinggi. Terbukti adanya perbedaan hasil sebelum dan sesudah diklat secara signifikan, dimana terhitung sebesar 13,246 sedangkan t tabel 2,861 (t hitung > t tabel). Ada penurunan angka anemia gizi besi antara sebelum (40%) dan sesudah pelatihan gizi (20%) p< 0,05, diukur selang enam bulan dari pelaksanaan pendidikan dan pelatihan gizi, dan terbukti ada perbedaan secara signifikan. Disarankan agar dilakukan pendampingan pasca pendidikan dan pelatihan gizi dan diperlukan penguatan dari tokoh masyarakat serta perangkat desa.